الاتحاد الأوروبي وآسيا الوسطى قضايا التعاون والشراكة الإستراتيجية - العبد الله, عمر; خليل, فادي; شمسين, فادي (Latakia University Journal - Economic and Legal Sciences Series, 2014)
ترّكز هذه الدراسة على الاستراتيجية الأمنية للاتحاد الأوروبي تجاه آسيا الوسطى كجزء من السياسة الخارجية والأمنية للاتحاد الأوروبي تجاه جمهوريات الاتحاد السوفيتي السابق. إنّها محاولة لإعادة تقييم إحدى أهم القضايا في العلاقات الدولية المعاصرة وهي التعاون بين الاتحاد الأوروبي وآسيا الوسطى قبل وبعد تبني "وثيقة الشراكة الاستراتيجية الجديدة بين الاتحاد الأوروبي وآسيا الوسطى" في حزيران 2007. حيث تُعّد هذه الاستراتيجية وثيقة سياسية مهمة في تاريخ العلاقات بين الطرفين. إنّ المرحلة الجديدة للتعاون بين الطرفين توّضح بشكل أكثر شمولية الأولويات التي أكدت عليها الإستراتيجية الجديدة، وتبين قضايا التعاون الإقليمي بين الجانبين مثل التنويع في مصادر الطاقة ومساراتها من منطقة آسيا الوسطى إلى أوروبا، ودورها في تحقيق أمن الطاقة لأوروبا. The Thesis focuses on the EU’s security strategy towards the Central Asian states – as part of the EU’s Common Foreign and Security Policy towards the post-soviet realm. The thesis analyses, assesses and scrutinises one of the topical issues of the contemporary international relations - cooperation between the European Union and Central Asian states before and after adoption in June 2007 of the ‘European Union and Central Asia: Strategy for a New Partnership’, an important political document in the history of relations between the two parties. The new stage of cooperation is analysed more comprehensively accentuating priorities set in the Strategy. Analysis of the regional cooperation between the European Union and Central Asian, issues of diversification of hydrocarbons supply routes from the region to Europe and provision of energy security.